2017
DOI: 10.12697/poa.2017.26.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning innovation in present and future of human anatomy course at RSU

Abstract: With the emerging presence of IT based technologies in medical education, virtual anatomy has become a part of medical teaching, learning and healthcare. Building on the foundation of strong basic sciences, teaching and learning, Rīga Stradiņš University (RSU) offers its students the Anatomage Table. The Department of Morphology enabled new possibilities and allowed students to learn anatomy through a high-quality and interactive 3D tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For all students, understanding the sizes of organs and relationships between them were reported as the most useful aspects of the Anatomage table. Understanding organ relationships was also the most positive feature reported by Kazoka andPilmane (2017), Hutchins (2017) and Custer and Michael (2015). Medical imaging students in the study by Custer and Michael (2015) reported that the "three-dimensional" dynamic nature of the images was most helpful in understanding organ relationships.…”
Section: Discussionmentioning
confidence: 91%
“…For all students, understanding the sizes of organs and relationships between them were reported as the most useful aspects of the Anatomage table. Understanding organ relationships was also the most positive feature reported by Kazoka andPilmane (2017), Hutchins (2017) and Custer and Michael (2015). Medical imaging students in the study by Custer and Michael (2015) reported that the "three-dimensional" dynamic nature of the images was most helpful in understanding organ relationships.…”
Section: Discussionmentioning
confidence: 91%
“…Over the years, however, new and more interactive methods to teaching anatomy have emerged and are used by students and anatomy educators [13]. The developmental intensity in technologies over the years has profoundly affected the teaching of Anatomy in the last decade and there is much debate about the suitable methods of delivering anatomical knowledge to students; hence the resolve by many medical tutors to use the three-dimensional display equipment [14]. The explosion of technologies during the last few decades has brought anatomical education into a new world [15, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Kažoka. D. et al [5] had investigated the usefulness and user satisfaction of using the Anatomage Table (Virtual Dissection Table) in teaching and learning of Human Anatomy course at Riga Stradis University, Riga, Latvia, and found that virtual dissection technology seems to have a promising role in future anatomy training. Fairén et al [6] had set up the VR system that allowed the nursing students to see and interact with the 3D model of human organs.…”
Section: Introductionmentioning
confidence: 99%